Comparison of the EUROIMMUN Dermatology Profile ELISA to the novel BIOCHIP Mosaic 7 for the diagnosis of immunobullous skin disease. (26th May 2021) - Simpson, Kate; Scardamaglia, Laura; Kok, Yonatan; Vu, Mi; Kidd, Daniel; Yap, Tami; Tran, Yang; Kern, Johannes S
Abstract: Background: The BIOCHIP is an indirect immunofluorescence diagnostic investigation which identifies multiple autoantibodies with a mosaic panel of target antigen‐specific substrates in a single incubation field. The EUROIMMUN Dermatology Profile ELISA allows simultaneous investigation of the six most important autoantibodies in bullous autoimmune dermatoses. Evaluation of the BIOCHIP Mosaic 7, compared to that of the EUROIMMUN Dermatology Profile ELISA, when used as a diagnostic investigation in pemphigus and pemphigoid, was undertaken in an Australian cohort. Methods: The serum of 27 patients was analysed including patients with pemphigus vulgaris ( n  = 10), pemphigus foliaceous ( n  = 4), bullous pemphigoid ( n  = 8), mucous membrane pemphigoid ( n  = 3) and negative controls ( n  = 2). Results of the BIOCHIP were compared with the EUROIMMUN Dermatology Profile ELISA, as well as with histology, direct immunofluorescence and indirect immunofluorescence. Results: In pemphigus vulgaris, sensitivity & specificity for the BIOCHIP Mosaic 7 were 100% and 94.1%, comparable to that of the EUROIMMUN Dermatology Profile ELISA with 80% sensitivity and 100% specificity. In bullous pemphigoid, sensitivity of the BIOCHIP was 87.5% and sensitivity of the EUROIMMUN Dermatology ELISA profile was 75%, whilst specificities for both diagnostic methods were 100% in our limited cohort. There was substantial or almost perfect concordance between the BIOCHIP Mosaic 7 and EUROIMMUN Dermatology Profile ELISA for pemphigus vulgaris and bullous pemphigoid. Conclusion: The BIOCHIP Mosaic 7 is a rapid, reliable diagnostic investigation in pemphigus and bullous pemphigoid. Results indicate it is comparable to the EUROIMMUN Dermatology Profile ELISA, whilst also providing additional testing with salt split skin, on one field.